Effect of ultra violet irradiation on the interplay between Th1 and Th2 lymphocytes - Abo Elnazar, Salma Y.; Ghazy, Amany A.; Ghoneim, Hossam E.; Taha, Abdul-Rahman M.; Abouelella, Amira M. (Frontiers in Pharmacology, 2015)
Although UV radiation is used to treat several diseases, including rickets, psoriasis, eczema and jaundice, prolonged human exposure to UV radiation may result in acute and chronic health effects on the skin, eye and immune system. Aim: this study is carried out to show the effect of UV on both splenocyte lymphoproliferative response and their capacity to produce IL-12 and IL-10 in mice. Methods: mice were exposed to whole body UVB and tested for the effect of recovery times on splenocyte proliferation and cytokine production. In addition, direct irradiation of spleens and lymphocyte suspension was done. Basal and mitogen-stimulated splenocyte proliferation was assessed by MTT assay while IL-10 and IL-12 were measured using ELISA. Results showed significant suppression in splenocyte proliferation in comparison with control. IL-12 levels were significantly reduced while IL-10 was increased. ConA and PWM had no significant changes in IL-10 while Con A caused a highly significant increase in IL-12 at day six recovery in UVB body irradiation. Conclusion: Exposure to UVB radiation could cause a state of immune suppression and shifts Th1/Th2 cell response. This effect is closely associated with the reduction of Th1 cytokines' expression and increase in Th2 cytokines' levels.